Utilizing the building envelope for power generation and conservation. (15th February 2016) - Lee, M.C.; Kuo, C.H.; Wang, F.J.
Abstract: Heat loading of the building envelope is caused by strong solar radiation and incorrect material selection. As a result of the heat loading of the building envelope, the indoor air temperature is increased, resulting in high energy consumption by air conditioners to maintain a comfortable indoor thermal environment. This study explores the use of a hybrid wall integrated with heat collectors (water piping system) and solar thermal power generators, which absorbs solar radiation through water to reduce heat transmission thereby saving energy and generating power. Power generation is achieved by an OD (oscillator device) that installed between a water tank (hot side) and building interior (cold side). The device acts by temperature differences between hot air (expansion) and cold air (contraction). CFD (computational dynamic simulation) was used to assess the effects of the hybrid wall on the interior environment. The results show that exterior heat is absorbed by cool water thereby reducing the heat transmission into the building, resulting in less energy consumption by air conditioners and power generation by use of temperature differences. Highlights: This study explores a hybrid building wall to save energy and generate power. Power generators operated by air pressure change via hot tank and cool interior. Less energy consumption by air conditioners and heating water. Performance of CFD simulated results and experiment results are similar. The energy saving efficiency is around 15 kWh/day via hybrid wall in west façade.